Investigation of Copy Number Variation in South African Patients With Congenital Heart Defects. (7th October 2022) - Saacks, Nicole A.; Eales, James; Spracklen, Timothy F.; Aldersley, Thomas; Human, Paul; Verryn, Mark; Lawrenson, John; Cupido, Blanche; Comitis, George; De Decker, Rik; Fourie, Barend; Swanson, Lenise; et al.
Abstract : Background: Congenital heart disease (CHD) is a leading non-infectious cause of pediatric morbidity and mortality worldwide. Although the etiology of CHD is poorly understood, genetic factors including copy number variants (CNVs) contribute to the risk of CHD in individuals of European ancestry. The presence of rare CNVs in African CHD populations is unknown. This study aimed to identify pathogenic and likely pathogenic CNVs in South African patients with CHD. Methods: Genotyping was performed on 90 patients with nonsyndromic CHD using the Affymetrix CytoScan HD platform. These data were used to identify large, rare CNVs in known CHD-associated genes and candidate genes. Results: We identified eight CNVs overlapping known CHD-associated genes ( GATA4, CRKL, TBX1, FLT4, B3GAT3, NSD1 ) in six patients. The analysis also revealed CNVs encompassing five candidate genes likely to play a role in the development of CHD ( DGCR8, KDM2A, JARID2, FSTL1, CYFIP1 ) in five patients. One patient was found to have 47, XXY karyotype. We report a total discovery yield of 6.7%, with 5.6% of the cohort carrying pathogenic or likely pathogenic CNVs expected to cause the observed phenotypes. Conclusions: In this study, we show that chromosomal microarray is an effective technique for identifying CNVs in African patients diagnosed with CHD and have demonstrated results similar to previous CHD genetic studies in Europeans. Novel potential CHD genes were also identified, indicating the value of genetic studies of CHD in ancestrally diverse populations.